2023
DOI: 10.3847/2041-8213/acb702
|View full text |Cite
|
Sign up to set email alerts
|

Density Profiles of Collapsed Rotating Massive Stars Favor Long Gamma-Ray Bursts

Abstract: Long-duration gamma-ray bursts (lGRBs) originate in relativistic collimated outflows—jets—that drill their way out of collapsing massive stars. Accurately modeling this process requires realistic stellar profiles for the jets to propagate through and break out of. Most previous studies have used simple power laws or pre-collapse models for massive stars. However, the relevant stellar profile for lGRB models is in fact that of a star after its core has collapsed to form a compact object. To self-consistently co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 59 publications
(61 reference statements)
2
8
0
Order By: Relevance
“…However, those shells will accelerate as they freefall and reach similar velocities. Importantly, the freefall time of those shells is 0.1 s, implying that after that time the progenitor structure is consistent with that of Halevi et al (2023). We have verified via a direct simulation that an 5 The accretion rate also increases with the BH mass,  ~~am v M ff 1…”
Section: Setupsupporting
confidence: 57%
See 3 more Smart Citations
“…However, those shells will accelerate as they freefall and reach similar velocities. Importantly, the freefall time of those shells is 0.1 s, implying that after that time the progenitor structure is consistent with that of Halevi et al (2023). We have verified via a direct simulation that an 5 The accretion rate also increases with the BH mass,  ~~am v M ff 1…”
Section: Setupsupporting
confidence: 57%
“…The stellar envelope undergoes solid body rotation well below the centrifugal value throughout the star, with the specific angular momentum given by 6 where r g ≡ GM/c 2 = 6.3 × 10 5 cm is the BH gravitational radius and ω 0 = 50 s −1 . We note that prior to the BH formation, Halevi et al (2023) found that the innermost (≈10 8.5 cm) stellar shells accelerate to high velocities. Since our simulations do not have self-gravity, we set the radial velocity to zero.…”
Section: Setupmentioning
confidence: 61%
See 2 more Smart Citations
“…Because the duration of a GRB (in the context of a black holedisk central engine) is roughly proportional to the amount of mass in the disk divided by its accretion rate 6 (i.e.,  T M M int ), longer-duration GRBs at lower redshifts imply these systems have more massive accretion disks, lower accretion rates, or both. Of course, extrapolating from the final state of the progenitor star (or stars) to the black hole-disk system that produces the GRB jet is not straightforward (Halevi et al 2022). However, we might expect general trends to hold -for example, a more extended massive star and/or one with an overall higher angular momentum reservoir may be able to produce a longer-lived jet upon collapse, leading to a longerduration GRB (see the recent arguments in Lloyd-Ronning 2022).…”
Section: Lloydmentioning
confidence: 99%